Harnessing Solar Energy for Hydrogen Generation: Advances in Artificial Photosynthesis - Belay Sitotaw Goshu; Melaku Masresha Woldeamaueal (Budapest International Research and Critics University, 2026)
Artificial photosynthesis offers a sustainable method for hydrogen production, addressing the environmental drawbacks of traditional methods like steam methane reforming (SMR). However, its commercialization faces challenges in efficiency, cost, scalability, and stability. This study aims to evaluate the performance, challenges, and commercialization potential of artificial photosynthesis, providing recommendations to establish it as a mainstream clean energy technology. The analysis includes visualizing STH efficiencies of PEC cells and photocatalysts, assessing scalability and longevity challenges, evaluating alternative catalysts, and analyzing environmental and economic impacts using Python-based visualizations like radar charts, bar plots, and line plots. Data from various systems and materials were compared against ideal benchmarks. BiVO₄ achieved the highest STH efficiency at 4.2%, but efficiencies remain below the 10% target. Scalability and stability issues are significant, with System C (Hybrid) showing a 22% efficiency loss after 12 months. Fe₂O₃ emerged as a cost-effective catalyst with a 30.0 mA/cm² per USD ratio. Artificial photosynthesis reduces CO₂ emissions by 18-fold compared to SMR and becomes cost-competitive by 2045. Commercialization gaps include cost (3 vs. ideal 7) and scalability (3 vs. 8). Artificial photosynthesis holds promise for a hydrogen-based economy but requires improvements in efficiency, cost, and scalability. Developing low-cost catalysts, enhancing stability, scaling production, improving efficiency, and increasing public awareness can bridge these gaps, with potential market readiness improvements of up to 25%.